DETERMINAN PERILAKU SEKSUAL REMAJA JALANAN DI KOTA MEDAN TAHUN 2019 - Sarmiati Sarmiati (Jurnal Komunitas Kesehatan Masyarakat, 2020)
Street teenage sexual behavior is at risk for contracting and transmitting sexually transmitted diseases such as HIV / AIDS and others. The purpose of this study was to quantitatively analyze the determinants of sexual behavior in street adolescents in the city of Medan. This type of research is an analytic survey with cross sectional study design. The population of 242 street teenagers is a sample of respondents characteristic of 100 street teenagers with total smapel techniques. Data collection techniques using a questionnaire. Data were analyzed univariate, bivariate and multivariate using multiple logistic regression tests at a significance level of 95%. Research results obtained that knowledge (p = 0,001) and attitude (p = 0,009) is a factor associated with risky sexual behavior of street adolescents in Medan and the results of multivariate analysis showed that the variable most associated with risky sexual behavior is attitude. The conclusions in this study were obtained that knowledge and attitudes are associated with risky sexual behavior. It is expected that street youth can live a good and orderly social life through positive activities.